Anthropometric Profile Of Rural Punjabi Women As Influenced By Their Dietary And Nutrient Intake (Applied Biological Research, 2017)
A cross sectional study was conducted on 154 moderately active adult women  belonging to low - (LIG), medium- (MIG) and high-income groups (HIG) from two villages namely Bharonwal Kalan and Bhatha Dhua of Ludhiana district  Punjab (India) in the year 2016. The data on dietary intake and anthropo metric profile were recorded among the three income groups. The intake of all the foods was inadequate, except for milk and milk products, among the women  of all income groups. The percent adequacy of protein among LIG, MIG and  HIG income groups was 89.2, 117.1 and 135.6, respectively, as compared to  RDA (recommended dietary allowances) while fat intake was much higher i.e.  05, 168 and 205%, respectively. Carbohydrate contributed 67, 62 and 60% to  the total energy intake in LIG, MIG and HIG, respectively. The mean body  mass index in LIG, MIG and HIG women was 21.4, 23.1 and 24.0 kg m-2,  respectively. A positively significant correlation was observed between intake  of cereals and pulses and weight of the subjects.
Keywords: Anthropometry; body mass index; correlation; dietary intake; obesity; women